2021
DOI: 10.1007/s00467-021-05139-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of an interdisciplinary tertiary center evaluation in children referred for suspected congenital anomalies of the kidney and urinary tract on fetal ultrasound - a retrospective outcome analysis

Abstract: Background Fetal ultrasound organ screening has become a standard of care in most high-income countries. This has resulted in increased detection of congenital abnormalities, which may lead to major uncertainty and anxiety in expectant parents, even though many of them are of minor relevance. In order to optimize prenatal counselling, we introduced an interdisciplinary approach for all pregnant women referred to our center by private obstetricians for a co-assessment of suspected relevant fetal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Važno ih je na vrijeme otkriti kako bi se preveniralo nepovratno oštećenje bubrega, a samim time i razvoj bubrežne insuficijencije. Zbog navedenog prenatalni i postnatalni ultrazvučni probir mokraćnog sustava ima važnu ulogu u ranom otkrivanju ovih anomalija 2,6 . Prenatalni ultrazvučni probir predstavlja veliki izazov u prenatalnoj dijagnostici s visokom stopom detekcije oko 90%, premda je uzrok i vrstu anomalije teže izdi ferencirati 6 .…”
unclassified
See 1 more Smart Citation
“…Važno ih je na vrijeme otkriti kako bi se preveniralo nepovratno oštećenje bubrega, a samim time i razvoj bubrežne insuficijencije. Zbog navedenog prenatalni i postnatalni ultrazvučni probir mokraćnog sustava ima važnu ulogu u ranom otkrivanju ovih anomalija 2,6 . Prenatalni ultrazvučni probir predstavlja veliki izazov u prenatalnoj dijagnostici s visokom stopom detekcije oko 90%, premda je uzrok i vrstu anomalije teže izdi ferencirati 6 .…”
unclassified
“…Zbog navedenog prenatalni i postnatalni ultrazvučni probir mokraćnog sustava ima važnu ulogu u ranom otkrivanju ovih anomalija 2,6 . Prenatalni ultrazvučni probir predstavlja veliki izazov u prenatalnoj dijagnostici s visokom stopom detekcije oko 90%, premda je uzrok i vrstu anomalije teže izdi ferencirati 6 . Zahvaljujući ranom ultrazvučnom skri ningu veliki dio anomalija mokraćnog sustava se rano otkrije, ali još uvijek postoji manji udio bolesnika u kojih se ove anomalije kasno otkriju i dovedu do zna čajnog oštećenja bubrežnog tkiva.…”
unclassified
“…Although it can be difficult to precisely predict postnatal kidney function from prenatal studies, prior research has identified some predictive features of neonatal kidney function based upon ultrasound and fetal biochemistry. [6][7][8] There are also established staging systems to assist maternal-fetal medicine clinicians and pediatric nephrologists with prenatal counseling and patient selection for in utero interventions. It is unclear if these studies are being used to assist with pediatric nephrology prenatal counseling and this should be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…An attractive question is the best time and kind of imaging workup of the babies. Many neonates with AH have normal postnatal sonography; an imaging study is unnecessary (7). On the other hand, some critical entities, such as severe UPJO, VUR, and posterior urethral valve (PUV), need early diagnosis and treatment to prevent severe complications (8).…”
Section: Introductionmentioning
confidence: 99%